2017
DOI: 10.1186/s12877-017-0426-3
|View full text |Cite
|
Sign up to set email alerts
|

Supporting clinical rules engine in the adjustment of medication (SCREAM): protocol of a multicentre, prospective, randomised study

Abstract: BackgroundIn the nursing home population, it is estimated that 1 in every 3 patients is polymedicated and given their considerable frailty, these patients are especially prone to adverse drug reactions. Clinical pharmacist-led medication reviews are considered successful interventions to improve medication safety in the inpatient setting. Due to the limited available evidence concerning the benefits of medication reviews performed in the nursing home setting, we propose a study aiming to demonstrate a positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…However, this type of technological support did not extend to supporting clinical decision-making. There was little data on the effect of CDSS in NHs, but there is ongoing research on this topic ( 83 ). Its impact in the long-term environment remains to be seen as recent trials on CDSS to optimize prescribing in primary and acute care have shown negative results on clinical outcomes [ 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this type of technological support did not extend to supporting clinical decision-making. There was little data on the effect of CDSS in NHs, but there is ongoing research on this topic ( 83 ). Its impact in the long-term environment remains to be seen as recent trials on CDSS to optimize prescribing in primary and acute care have shown negative results on clinical outcomes [ 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…The COME-ON cRCT is a complex, multifaceted intervention, including interdisciplinary case conferences, on the appropriateness of prescribing of medicines in Belgian nursing homes [34]. The SCREAM study aims to use a computerised clinical support system that analyses the NHR’ medications in terms of interactions, dose appropriateness and other clinical data to reduce the time resources for medication reviews by pharmacists and nursing home physicians [35]. Our study’s emphasis is on the combination of a standardised pharmacist-led medication review and changing interprofessional cooperation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Yang et al (2018) proposed reminder systems, based on patients' allergy background, to prevent hypersensitivity reactions to radiocontrast media, according to the Korean health policy. Gonzalvo et al (2017) proposed a DDSS based on the CONSORT guidelines, providing treatment recommendations for poly-medicated patients. Another well-known example is DxPlain (Barnett et al, 1987;Hoffer et al, 2005), an early DDSS dedicated to providing recommendations for primary care, which is still available 5 .…”
Section: A Loss Of Confidence In Physicians' Diagnostic Skills and Knmentioning
confidence: 99%